COMPETITIVE ADVANTAGE STRATEGY IN GROCERY STORE BUSINESS OF ENTREPRENEURS IN KHLONG KRACHAENG SUBDISTRICT, MUEANG DISTRICT, - Panboonlue, Nuttaphong (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2019)
The objectives of this research are to study the grocery store business model in Khlong Krachaeng Subdistrict, 44Mueang District, Phetchaburi Province, to study the competitive environment of grocery store in Khlong Krachaeng Subdistrict, 4 4Mueang District, Phetchaburi Province and to study the Competitive advantage of grocery store business in Khlong Krachaeng Subdistrict, 44Mueang District, Phetchaburi Province. This research is a qualitative research method with in - depth interview for four entrepreneurs and two convenience store managers in Khlong Krachaeng Subdistrict, 44Mueang District, Phetchaburi Province. The research instrument was an interview form by using open-ended questions to collect data based on the descriptive analysis which analyzed and recorded from the interview, then classified into categories and analyzed the data according to the concept to find the conclusion. The result of this study are that 1) The grocery store business model is a registered trademark by a single owner who manages the business on their own. This type of business uses low cost, and easy to manage. 2)The competitive environment of grocery store business was found that the entrepreneurs made an adjustment by creating an understanding and loyalty among their customers in the business. In addition, customers can find materials or products by comparing the seller's bargaining. 3)The competitive advantage of grocery store business was found that the sellers and their customers communicate about product information to create purchasing attitude and behavior. Moreover, they manage by considering the profits of the business, determine the exact price, focusing on services and customer convenience.